Crop-animal interactions in mixed farming systems in Asia - Devendra, C.; Thomas, D. (Elsevier, 2002)
The integration of crop and animal production is well developed in the farming systems of Asia, particularly those in small-scale agriculture. There is marked complementarity in resource use in these systems, with inputs from one sector being supplied to others. Specific examples of the main crop¯animal interactions are given for different countries, and reference is made to the results of a number of case studies. These have demonstrated the important contribution that animals make to increased production, income generation, and the improved sustainability of annual and perennial cropping systems